Analisis Penerapan Akuntansi Lingkungan Terhadap Pengelolaan Limbah Pada PT. Multi Hanna Kreasindo - Jihan Mawaddah; Putri Permata Sari; Paradilla Sandi Br Bangun (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the application of environmental accounting to waste management at PT. Multi Hanna Kreasindo. The method used in this research is a descriptive analysis method with a qualitative approach. The type of data used in this research is secondary data, where the data comes from research journals that have been reprocessed. Based on the research results, it shows that the company has presented and disclosed information related to waste management carried out in its operational activities.